The Influence of Tour Packages and Service Quality on Tourist Satisfaction Through Purchase Decisions as a Mediating Variable at Munajad Wisata Tour and Travel, Bandar Lampung - Afrida Jayanti; Satria Bangsawan; Yuniarti Fihartini (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Intensifying competition in the tourism travel service industry requires agencies to improve tour package quality and service delivery to sustain customer purchase decisions and satisfaction. This study examines the effects of tour packages and service quality on purchase decisions and tourist satisfaction at Munajad Wisata Tour and Travel in Bandar Lampung, while also assessing the mediating role of purchase decisions. A quantitative survey was conducted with 385 respondents selected through purposive sampling, and the proposed relationships were analyzed using Partial Least Squares–Structural Equation Modeling. The results show that tour packages and service quality positively influence purchase decisions and tourist satisfaction. Purchase decisions also exert a positive effect on tourist satisfaction and significantly mediate the relationships between tour packages, service quality, and satisfaction. These findings indicate that customer satisfaction is shaped through both direct service evaluations and the purchasing process. The study contributes to tourism marketing research by demonstrating the central role of purchase decisions in translating package and service attributes into tourist satisfaction. Managerially, travel agencies should strengthen package relevance, service reliability, and customer experience to improve both conversion and satisfaction.